PRODUCT PLACEMENT IN MOVIES: EFEKTIFITAS SUBLIMINAL ADVERTISING - SETIAWAN A., . (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Product placement is a form of strategy that many companies show how the product as if it was part of a movie or television show. Product placement in the movie is a form of subconscious or subliminal advertising, where ads are done with the unconscious affect the subconscious of consumers (a member of the audience), through accepted material in movie or drama, where the movie and the drama include certain product placement. Product placement can be divided into three types, namely: 1) an Implicit Product Placement; 2) Integrated Explicit Product Placement; and 3) Non Integrated Explicit Product Placement. This type of use of the strategy of product placement within the context of a film can be done through three ways: 1) Presents a clear overview of the product and brand-name products; 2) use the product or brand in the film; and 3) is used and discussed in the dialogue of the film by the actor.